Improving Students’ Reading Comprehension By Using Numbered Head Together (NHT) Strategy in SD IT Fadilah Pekanbaru - Yeni Afriyeni (Universitas Pahlawan Tuanku Tambusai, 2020)
This action research is aimed at improving the students‘ reading comprehension by using Numbered Head Together (NHT) strategy in five (A) grade at SD IT Fadilah in Pekanbaru. The researcher applies the discussion method in learning English at SD IT Fadilah Pekanbaru. Numbered Head Together (NHT) or numbering thinking together is a type of cooperative learning that is designed to influence patterns of interaction and as an alternative to classroom. The result shows that the use of NHT strategy has successfully made the students able to comprehend the reading. It can be seen from student learning outcomes obtained a value of 54.60 with a low category, in UH I increased learning outcomes with the acquisition of value of 65.76 in the medium category, and in UH II student learning outcomes increased again with the acquisition of a value of 79.25 with high category. Based on the above research data, it appears that student learning outcomes in English have improved after the Number Head Together (NHT) strategy was applied. The Numbered Head Together (NHT) strategy generally involves students in reviewing the material in the lesson and understanding of the material provided.